HUBUNGAN FEAR OF MISSING OUT (FOMO) DENGAN PERILAKU KONSUMTIF PADA MAHASISWA PENGGUNA MEDIA SOSIAL TIKTOK DI UNIVERSITAS MUHAMMADIYYAH GORONTALO - Adinda Kariem Kambey; Lenny Syamsuddin; Fahri Kamuli (Psikodidaktika, 2026)
This study aims to determine the relationship between Fear of Missing Out (FOMO) and consumptive behavior among students who use TikTok social media at Universitas Muhammadiyah Gorontalo. This research employed a quantitative approach with a correlational method. The population in this study consisted of 357 students from various academic majors, all of whom were selected as the research sample using a purposive sampling technique. Data collection was conducted using the Fear of Missing Out (FOMO) scale developed based on the aspects proposed by Przybylski et al. (2013), as well as a consumptive behavior scale based on the aspects proposed by Lina and Rosyid (1997). The data were analyzed using the Spearman Rank correlation test. The results of the analysis showed a positive and significant relationship between Fear of Missing Out (FOMO) and consumptive behavior, with a correlation coefficient value of 0.565 and a significance value of 0.000 (p < 0.05). These findings indicate that the relationship falls within the moderate category. In addition, the coefficient of determination (R²) value was 0.331, indicating that Fear of Missing Out contributed 33.1% to consumptive behavior. In other words, the higher the level of Fear of Missing Out (FOMO), the higher the tendency toward consumptive behavior.